Paper-Based System for Ion Transfer Across the Liquid-Liquid Interface - Podrazka, M.; Nery, E.; Pacowska, A.; Arrigan, Damien; Jönsson-Niedziólka, M. (American Chemical Society, 2018)
While ion transfer studies were shown to be a promising method for fundamental electrochemistry, pharmacokinetic studies, and sensing, they suffer from inherent instability of the interface formed between the organic and aqueous phases. This limits to some extent the range of solvents which can be used and confines these studies to the laboratory. We propose here the use of paper, which has revolutionized the way we think of miniaturized analytical devices during the past decade, as a perfect substrate for ion transfer studies across the liquid-liquid interface. We describe the design of a simple three-phase electrode paper-based setup for redox-driven transfer of anions from an aqueous to an organic phase. Electrochemical measurements of seven different anions and concentration dependence studies are in good agreement with the results obtained with traditional setups. Additionally, we show the applicability and limitations of such setups to the analysis of anion mixtures.